Objeto virtual de aprendizaje para fortalecer el proceso de enseñanza aprendizaje de la asignatura informática - Sizalima Logacho, Joel Abraham; Coronel Ontaneda, Steeven Ismael (Machala, Utmachala, 2023)
Virtual learning objects are immersed in society in various areas of life, in which it has more impact on education as it is favorably changing the way of teaching. Educational tools have been of great importance for this process of transformation of education, which changed the traditional way of teaching where the teacher came and explained his classes regardless of whether the student learns or not, nowadays with the implementation of the tools teachers become a support for students, but it is also a challenge for teachers as they have to educate themselves to obtain adequate knowledge about the new tools and thus can instruct in a correct way to the student. The objective of this research is the development of a virtual learning object to strengthen the teaching-learning process in the subject of Computer Science. As main actors we have the students of the second year of high school parallel A and the teacher in charge of the classroom belonging to the Colegio de Bachillerato "Dr. Camilo Gallegos Domínguez". The methodology used in this research is the ADDIE model and a Pre-test and Post-tests were also used. For data collection, two surveys were used, both were used in the two experiences, one with the teacher and the other with the students, which consists of conducting a demonstration class using the Virtual Learning Object (VLO). At the "Dr. Camilo Gallegos Dominguez" High School, problems were diagnosed in the 3rd BGU classroom, in the subject of computer science applied to education, where students had a deficit in learning, in addition to lack of attention and disinterest in the class, they did not present their homework on time. This OVA was developed with the purpose of creating content, with the objective of strengthening the teaching process and that they can have a better feedback in class. The purpose of this study is to develop a virtual learning object as a pedagogical support within the subject of Computer Science applied to education, because it is important to develop resources to help students learn in a practical and pedagogical way. Taking into account the transforming vision of society, the inclusion of ICT in the classroom is necessary, therefore, as students of the Faculty of Social Sciences, we propose to create virtual learning objects to support the teaching of the subject, where students will become communicative, interactive and more autonomous elements, develop skills and competencies and form their own knowledge. The results obtained showed that the OVA effectively gave a positive change in the classroom, increased participation and attention of students as well as there was a communication between teacher and student, it is also expected that students learn to use it correctly in education digital resources, on the other hand the teacher in charge of the subject was willing to include more often in classes as she saw that the result was favorable and thus the OVA had a better impact on students.
Los objetos virtuales de aprendizaje se encuentran inmersos en la sociedad dentro de varios ámbitos de la vida, en el cual tiene más impacto en la educación ya que está cambiando favorablemente la manera de enseñar. Las herramientas educativas han sido de gran importancia para este proceso de transformación de la educación, en la cual se cambió esa forma tradicionalista de enseñar donde el docente llegaba y explicaba sus clases sin importar si el estudiante aprenda o no, en la actualidad con la implementación de las herramientas los docentes pasen a ser un apoyo para los alumnos, pero también es un reto para los docentes ya que tienes que auto educarse para poder obtener los conocimientos adecuados sobres las nuevas herramientas y así pode instruir de una manera correcta al alumno. En el Colegio de bachillerato “Dr. Camilo Gallegos Domínguez” se diagnosticó problemas en el aula de clases de 3er BGU, en la asignatura de informática aplicada a la educación, donde los estudiantes tenían un déficit en el aprendizaje, además la falta de atención y de desinterés por la clase, no presentaban las tareas a su debido tiempo. Este OVA fue desarrollado con la finalidad de crear contenido, con el objetivo de fortalecer el proceso enseñanza y que puedan tener una mejor retroalimentación en clases. El objetivo de esta investigación es el desarrollo de un objeto virtual de aprendizaje mediante el uso de la herramienta Google Sites para el fortalecimiento del proceso enseñanza-aprendizaje de la asignatura de Informática. Como principales actores tenemos a los estudiantes de segundo de bachillerato paralelo A y la docente encargada del aula perteneciente al el Colegio de Bachillerato “Dr. Camilo Gallegos Domínguez”. En esta investigación se utilizó un enfoque cuantitativo y cualitativo, también conocido como enfoque mixto implementando un Pre-test y Post-tes, con el modelo de investigación ADDIE . Para la recolección de datos se usó dos encuestas, ambas se utilizaron en las dos experiencias una con la docente y otra con los estudiantes la cual que consiste en realizar una clase demostrativa haciendo uso del Objeto Virtual de Aprendizaje (OVA). Los resultados obtenidos demostraron que el OVA efectivamente dio un cambio positivo en el aula de clases, aumentó la participación y la atención de los estudiantes así mismo existió una comunicación entre docente y alumno, también se espera que los estudiantes aprendan a usarla de manera correcta en la educación los recursos digitales, por otro lado la docente a cargo de la asignatura se encontraba dispuesta a incluir más seguido en clases ya que vio que el resultado fue favorable y de esta manera el OVA tuvo un mejor impacto en los estudiantes
Keywords: RECURSO EDUCATIVO; ESTRATEGIA; APRENDIZAJE; INTERACCION; MOTIVACION